PENGARUH MARKET POWER DAN CORPORATE GOVERNANCE TERHADAP FUTURE EARNINGS RESPONSE COEFFICIENT PADA PERUSAHAAN DI BURSA EFEK INDONESIA - Ellisa Putri Mita Pradhana; Etty Murwaningsari (Jurnal Akuntansi Trisakti, 2014)
This research aimed to analyze the influence of Market Power and CorporateGovernance to the FERC with Leverage as an intervening variable. The samples in this study were 203 manufacturing companies listed on the IDX. This research used Structure Equation Modeling (SEM) to analyze the influence of independent variables to dependent variable with intervening variable. The results are, market power has a negative significant influence to the FERC, corporate governance measured by board of commissioner and board size have an insignificant influence to the FERC, and corporate governance measured by internal auditor has a positive significant influence to the FERC.